background image

3.2.1

The proof for

n

= 0

In this case a multifuncoid

f

of the form

Z

=

P

0

=

{

()

}

is an element of the set

P

B

0

=

{{

()

}}

that is

f

=

{

()

}

. Obviously

f

is an upper set. Then

E

f

=

L

F

0

|

up

L

f

 

=

{

()

|

up ()

⊆ {

()

}}

=

{

()

|

{

()

} ⊆ {

()

}}

=

{

()

}

.

For

i

= dom

F

0

we have (val

f

)

i

L

is a free star just because

i

doesn’t exist.

Obviously

E

f

is an upper set.

So

E

f

is a multifuncoid of the form

F

0

.

3.2.2

The proof for

n

= 1

We will use notation from [2].

Lemma 1

The upgrading (regarding the filtrator

(

F

;

P

)

) of every free star on

P

is a free star on

F

.

Proof

Let

f

is a free star on

P

. Then (theorem 45 in [2]) there exist a

g

F

such that

∂g

=

f

.

E

f

=

{

L

F

|

up

L

∂g

}

=

{

L

F

|

L

6≍

g

}

. It remained to prove

that

{

L

F

|

L

6≍

g

}

is a free star.

Obviously 0

F

6∈ {

L

F

|

L

6≍

g

}

.

For every

A, B

∈ {

L

F

|

L

6≍

g

}

we have

A

B

∈ {

L

F

|

L

6≍

g

} ⇔

(

A

B

)

g

6

= 0

F

(

A

g

)

(

B

g

)

6

= 0

F

A

g

6

= 0

F

B

g

6

= 0

F

A

{

L

F

|

L

6≍

g

} ∨

B

∈ {

L

F

|

L

6≍

g

}

.

The proof is finished.

Let

Q

be the set of all multifuncoids of the form

A

1

where

A

is a join-

semilattice with least element. Then

f

Q

if and only if (val

f

)

0

is a free

star.

But (val

f

)

0

=

{

X

A

|

{

(0;

X

)

} ∈

f

}

=

{

X

A

|

f

0 =

X

}

=

f

0.

So it uis easy to show that the filtrator of the form

F

1

FCD;

P

1

FCD

is

isomorphic to the filtrator (

F

Star;

P

Star).

Thus by the lemma upgrading a multifuncoid of the form

P

1

is a multifuncoid

of the form

F

1

.

3.2.3

The proof for

n

= 2

An

f

is a (finitary) multifuncoid of the form

A

×

B

(for

A

,

B

being join-

semilattices with least elements) iff all the following:

1. (val

f

)

0

L

is a free star for every

L

=

{

(1;

Y

)

}

where

Y

B

;

2. (val

f

)

1

L

is a free star for every

L

=

{

(0;

X

)

}

where

X

A

;

what is equal to the following:

1.

{

X

A

|

X f Y

}

is a free star for every

Y

B

;

5